FAKTOR-FAKTOR YANG MEMPENGARUHI KESEHATAN MENTAL EMOSIONAL PADA ANAK USIA SEKOLAH - Dwi Laila Ranti; Fathra Annis Nauli; Ganis " Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Mental and emotional health is a state of healthy individuals mentally and emotionally where individuals can utilize cognitive abilities and emotions with early detection using Questionnaires Emotional Mental Problems (KMME). This study aims to identify the correlation with the external factors emotional mental health in primary schools 55 Pekanbaru design descriptive study using cross sectional correlation. Samples are 64 pupils, grades 4 and 5 were taken based on inclusion criteria using proportionate stratified random sampling technique. The data analysis used univariate analysis to determine the frequency distribution and bivariate using chi-square test. The results showed that there is no correlation between parenting style, school climate, and peer support with emotional mental health in school-aged children. Results of statistical correlation parenting style with emotional mental heatlh in school-age children was obstained (p=0,465 > a=0,05), correlation school climate with emotional mental health in school-age children was obtained (p=1,000 > a=005), correlation peer support with emotional mental health in school-age children was obtained (p=0,196 > a=0,05) were meaning that there is no correlation among all the variables with emotional mental health in school-age children with the results of 50 respondents (78.1%) had a poor emotional mental health. The results of this study recomend teachers and parents to detected emotional mental disorders can be early. Key words: factors affecting, mental emotional, school age